The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1002/pssb.201800284
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Band Offset on the Property and Operation of the Potential Well Barrier Diodes

Abstract: The impact of grading the GaAs/AlGaAs interface on carrier dynamics in a potential well barrier (PWB) diode has been explored and demonstrated in this paper. Three heterostructures in the GaAs/AlGaAs system namely GaAs/Al0.2Ga0.8As, GaAs/Al0.3Ga0.7As, and GaAs/Al0.4Ga0.6As with corresponding band offsets of 0.10, 0.25, and 0.30 eV, respectively, are investigated using the drift‐diffusion (DD) and Monte Carlo (MC) models. The behavior of the diodes with different band offsets are compared in terms of mean elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Due to the similarity in the principle of operation of a PWB and PDB diodes and also, because it was found that considering hot electron effects was important in these devices at very high electric fields [7][8][9] , it becomes imperative to consider hot electron effects in the PWB diode. Previous papers have investigated the operation of potential well barrier diode using drift-diffusion models [5,10,11] , with the MC model treated in Ref. [12] though, no energy transport or heating effects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the similarity in the principle of operation of a PWB and PDB diodes and also, because it was found that considering hot electron effects was important in these devices at very high electric fields [7][8][9] , it becomes imperative to consider hot electron effects in the PWB diode. Previous papers have investigated the operation of potential well barrier diode using drift-diffusion models [5,10,11] , with the MC model treated in Ref. [12] though, no energy transport or heating effects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Just like Planar Doped Barrier diodes (PDB) [1], [2] and other heterostructure barrier devices, Potential Well Barrier diodes (PWB) studied in [3][4][5][6] have shown prospects of applications in detector and mixers. The diode has a lot of advantages compared to similar devices for the same purpose.…”
Section: Introductionmentioning
confidence: 99%